Catalytic reaction of mediated oxidation in ethylbenzenes and benzyl alcohol using gold supported on zinc oxide catalyst / Afiq Anwar - Afiq , Anwar (2022)
Gold nanoparticles of 3 nm supported on zinc oxide was synthesized by urea deposition precipitation then utilized as a catalyst in ethylbenzene and benzylalcohol oxidation using tert-butyl hydroperoxide as the oxidant in acetonitrile solvent. The catalyst gave more than 50% conversion and high selectivity towards acetophenone (50%) as the major product but moderate selectivity towards other products such as 1-phenylethanol, benzaldehyde, benzoic acid, and other compounds in 5 mL acetonitrile solvent at 100 °C for 24 hours reaction. The catalyst showed high selective for benzylalcohol oxidation with 60.3 % conversion and 100 % selectivity towards benzaldehyde. The fresh and spent catalysts were comprehensively characterized by XRD, HRTEM, XRF, BET and ATR-IR to correlate the catalyst activity. Factors affecting the catalytic activity in ethylbenzene oxidation such as gold loading, calcination treatment at 300 °C, type of solvent, reaction time, reaction temperature, oxidant to ethylbenzene molar ratio, catalyst weight and solvent volume were studied. The gold nanoparticle introduces a very selective reaction pathway and is an environmentally friendly catalyst as the oxidant used is less harmful.